Quality Management in Chinese Privately Owned Small and Medium-Sized Enterprises - Weiguang, Ying (2012)
In this paper the author tried to explore the current situation of the Quality Management (QM) development in Chinese privately-owned SMEs. The specific question which the author wanted to answer is that: how did the company owners value the currently prevailing QM tools and systems? To answer this question the author arranged individual interviews with company owners/managers from six different Privately-owned SMEs. These interviewees were asked to accomplish a verbal survey about their opinions towards QM tools and systems along with a numerical questionnaire rating the factors affecting their decision on whether to adopt a QM system or not. In this research the author found that there were two bottlenecks in the implementation of QM and the top manager ideology was of the most importance for quality strategy implementation.